2002
DOI: 10.1093/intimm/dxf060
|View full text |Cite
|
Sign up to set email alerts
|

Isoforms of the class II transactivator protein

Abstract: The class II transactivator (CIITA) controls both the constitutive and IFN-gamma inducible expression of HLA-D genes. In addition, through the squelching of another transactivator CREB-binding protein, CIITA was more recently shown to have a wider cellular function, including cell cycle control or cellular response to IFN-gamma and IL-4. However, due to its low expression level, its analysis mainly relies on the study of recombinant overexpressed forms of the protein. We report here the analysis of native CIIT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…In some experiments, CIITA protein was detectable at 2 hours and the level was reduced at 24 hours, peaking between 6 and 24 hours, similar to other cells. 28,29 RFX5, a DNA-binding protein that recruits CIITA, is constitutively expressed and induced (3-fold) with time by IFN-␥ in aortic SMCs (supplemental Figure II). These results show that SMCs produce a significant amount of IFN-␥ inducible CIITA and RFX-5 and that CIITA types III and IV are the foremost isoforms present in this cell type.…”
Section: Human Aortic Smcs Express Two Ciita Isoforms That Are Highlymentioning
confidence: 99%
“…In some experiments, CIITA protein was detectable at 2 hours and the level was reduced at 24 hours, peaking between 6 and 24 hours, similar to other cells. 28,29 RFX5, a DNA-binding protein that recruits CIITA, is constitutively expressed and induced (3-fold) with time by IFN-␥ in aortic SMCs (supplemental Figure II). These results show that SMCs produce a significant amount of IFN-␥ inducible CIITA and RFX-5 and that CIITA types III and IV are the foremost isoforms present in this cell type.…”
Section: Human Aortic Smcs Express Two Ciita Isoforms That Are Highlymentioning
confidence: 99%
“…These experiments were performed in the HeLa cell line in which we have shown that recombinant CIITA is expressed at levels close to physiological ones. 16 Functional complementation of this cell line is therefore useful as it allows to discriminate fully invalidating defects from leaky mutations. 48 We additionally have examined the level of CIITA protein expression in the transfected clones without evidencing any reduction when compared to cell clones transfected with the wild-type cDNA (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…As previously reported by our group, CIITA is expressed in the Raji cell line as two isoforms, B-CIITA and F-CIITA, where B-CIITA is 24 amino acids longer in its N-terminal extremity due to an alternative usage of translation initiation codons. 16 The RJ2.2.5 cell line presents defects in both alleles of MHC2TA.…”
Section: Ciita Protein Expression Is Strongly Reduced In the Rec-1 Cementioning
confidence: 99%
See 1 more Smart Citation
“…17,18,31,32 In Ovx-B6 mice, significant CIITA mRNA expression in the salivary and lacrimal gland tissues was observed respectively at 2 weeks and 3 weeks after ovariectomy, and later declined with age by quantitative RT-PCR analysis ( Figure 1C). CIITA has three different isoforms synthesized from different, cellspecific promoters 33 ; promoter I is mainly used in dendritic cells, promoter III in B lymphocytes, and promoter IV in nonhematopoietic cells. The CIITA expression was controlled by each promoter referred to as type I, III, and IV.…”
Section: Tissue-specific Mhc Class II Expressions In the Exocrine Glamentioning
confidence: 99%